Investigating Positive Psychology Approaches in Case Management and Residential Programming With Incarcerated Youth - Cross, Lara E.; Morrison, William; Peterson, Patricia; Domene, José F. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article examines how a rural Canadian secure custody facility for youth implemented positive psychology principles in its case management protocols and residential programming. A directed content analysis design was utilized to identify specific factors of positive psychology in the facility’s policy and programming manual, as well as in interviews with 10 youth and 11 service providers at the facility. Data revealed numerous positive psychology factors were incorporated in various ways at the facility, particularly person-centred care, autonomy, and relatedness/connectedness. Differences among policy documentation, youth, and service provider perceptions were found, as well as challenges regarding intent versus effect of programming. Implications for practice and directions for future research are discussed.